Pre-surgical Orthopedic (PSO) Pre-maxilla Appliance for Children with Cleft Lip and Palate: A Case Series - Saskianti, Tania; Amalia, Rizki; Limbri, Stephanie Clara; Dewi, Ardianti Maartrina; Tedjosasongko, Udijanto (Indonesian Journal of Dental Medicine, 2018)
Background: Cleft lip and palate is one of most common craniofacial anomalies. It is a congenital defect and can be resulted from genetic mutation, environment and multifactor causes. The problems of cleft lip and palate on baby complicate as poor feeding ability can lead to growth and development disturbances. Purpose: This article described the use of PSO in a 4-day old male neonate with unilateral cleft lip and palate and a 3- year old male child with soft and hard palate cleft, both with chief complaint of feeding difficulty. Case Management: Custom tray was used to deliver the alginate impression. The appliance was both fabricated using self-cured acrylic and with / without lip strapping. Discussion: Pre-surgical orthopedic appliances are most frequently provided by the pediatric dentist on cleft palate teams at most hospital-based programs. Conclusion: The PSO appliance could approximate the segments of the cleft maxilla by allowing spontaneous growth of palatal shelves prior to the reconstructive and definitive surgery.